1990
DOI: 10.1111/j.1600-0773.1990.tb00750.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Distribution of Three Bisphosphonates in Mice

Abstract: The distribution of approximately equipotent doses of 14C-labelled clodronate (0.1 mmol/kg), etidronate (0.1 mmol/kg), and amidronate (0.015 mmol/kg), and also an equimolar dose of amidronate (0.1 mmol/kg), was studied in mice by measuring the 14C-activities in various tissues up to 360 days after a single intravenous injection. With the higher dose of amidronate the distribution could be, however, monitored only for 7 days because of the toxicity of the drug. The results indicate that there are major differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 13 publications
0
43
0
1
Order By: Relevance
“…2) However, it should be noted that Eti and Clo are not retained at all within soft-tissues after their intravenous injection into mice, although a small quantity of Pam (N-BP) is retained for a few days. 25) These results suggest that non-N-BPs are hardly taken at all into soft-tissue cells, while N-BPs are taken into such cells, even if in smaller amounts than in bone. In our previous studies in which we used ear-pinnas for examining inflammation, Eti and Clo were found to reduce the inflammatory effects of both the non-cyclic N-BP Ale and the cyclic N-BPs Zol and Min.…”
Section: Modulating Effects Of Non-n-bps On the Inflammatory Effects mentioning
confidence: 70%
“…2) However, it should be noted that Eti and Clo are not retained at all within soft-tissues after their intravenous injection into mice, although a small quantity of Pam (N-BP) is retained for a few days. 25) These results suggest that non-N-BPs are hardly taken at all into soft-tissue cells, while N-BPs are taken into such cells, even if in smaller amounts than in bone. In our previous studies in which we used ear-pinnas for examining inflammation, Eti and Clo were found to reduce the inflammatory effects of both the non-cyclic N-BP Ale and the cyclic N-BPs Zol and Min.…”
Section: Modulating Effects Of Non-n-bps On the Inflammatory Effects mentioning
confidence: 70%
“…10) Indeed, the non-N-BPs etidronate and clodronate almost completely lack inflammatory and necrotic effects in mice, 7,16) and they are hardly retained at all within soft-tissues in mice after intravenous injection. 17) On the contrary, they antagonize the entry of N-BPs into softtissues. 12,16,18) Hence, etidronate and clodronate can reduce or prevent the inflammatory/necrotic effects of N-BPs, whether these occur following administration of N-BPs or their release from sites that have already accumulated them.…”
Section: Discussionmentioning
confidence: 99%
“…(i) N-BPs inhibit farnesyl pyrophosphate synthase in the mevalonate pathway during cholesterol synthesis, leading to cytotoxicity, including apoptosis, and reduced prenylation of proteins. 17,14) Thus, N-BPs are by themselves inflammatory and necrotic, and they directly injure soft-tissue cells. 8,15,16) (ii) BPs (both N-BPs, non-N-BPs) accumulate within bone after repeated administration, especially within inflamed bones.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies on bisphosphonate biodistribution by Mönkkönen et al [110], with radiolabelled compounds showed that bisphosphonates are not excreted immediately by the kidneys, but are primarily taken up by the bone with the possibility that some may also be taken up by soft tissues such as the spleen, liver and kidney.…”
Section: Distributionmentioning
confidence: 99%